The Regulation of Direct-to-Consumer Genetic Tests - Kaye, Jane (2008)
The past year has been marked by the emergence of several companies, such as 23andMe, deCODEME, Navigenics and Knome, offering tests using genome-wide technology direct to consumers over the internet. Based on published research findings of GWAS and other studies, these companies will calculate an individual's risk to a number of common diseases, without the necessity of going through a medical practitioner. One of the significant challenges of direct-to-consumer testing is that shifts the control of genetic testing from the clinical domain and medical professionals into the hands of consumers. No longer is genetic testing being carried out solely for medical reasons, by specialists in clinical genetics. Testing is now being used to empower consumers and can be used ‘to shed new light on your distant ancestors, your close family and most of all, yourself’ (23andMe). Such information can be shared with family and friends for ‘fun’, as part of the new ‘recreational genomics’. Direct-to-consumer testing challenges many of the assumptions that underpin current practice surrounding genetic tests while at the same time exposing the deficiencies in the current regulatory frameworks to regulate this area. The purpose of this paper is to explore some of these issues, at a time when the science and the law are changing rapidly.